Analgesic efficacy of tapentadol in chronic joint disorders in horses: plasma serotonin concentration and adrenocortical response as biomarkers of pain-induced stress - Costa, Giovanna Lucrezia; Tabbì, Marco; Bruschetta, Giuseppe; Spadola, Filippo; Leonardi, Fabio; Bruno, Fabio; Iannelli, Nicola Maria; Licata, Patrizia; Macrì, Francesco; Passino, Eraldo Sanna; Macrì, Daniele; Interlandi, Claudia (Frontiers in Veterinary Science, 2024)
The study aimed to evaluate the analgesic efficacy of tapentadol in horses, by determining plasma serotonin concentration and adrenocortical response, as biomarkers of pain stress in chronic joint disorders. Thirty-six horses (20 females and 16 males) were divided into three groups of 12 subjects each: group A, osteoarthritis (OA), grade 3–4 lameness; group B, OA, grade 5 lameness; and group C, no OA, no lameness, were enrolled. The orthopedic examination included flexion tests, and radiological and ultrasound examinations. The degree of lameness has been estimated from 0 to 5 according to the American Association of Equine Practitioners (AAEPs). Heart and respiratory rates (HR and RR) and blood pressure were recorded. Serotonin concentration and circulating cortisol levels were determined at baseline and the end of every week for 4 weeks. Biochemical parameters were recorded at baseline and the end of treatment with tapentadol. Subjects with OA were treated with tapentadol 0.5 mg kg−1. The response to painful stimulus on flexion tests was evaluated using the modified numeric pain rating scale (modified NRS 0–7) from baseline and the cumulative pain score (CPS 0–4) after the first week of treatment with tapentadol. The lameness decreased throughout the timeline in both groups (score from 3–4 to 1 in group A and score from 5 to 1 in group B) (p < 0.05). The NRS score decreased throughout the timeline (p < 0.05), from mild pain to no pain in group A (score 1–3 to 0) and from moderate pain to no pain in group B (score from 4 to 0). Physiological variables remained within the physiological range throughout the timeline. Cumulative pain scores ranged from 0.5 to 4 in group A and 1.5 to 7 in group B (p = 0.008). Serotonin concentrations remained unchanged throughout the timeline in all groups (p = 1.000) but in the OA groups, the concentrations were lower than control (p < 0.001). Circulating cortisol levels were reduced compared to baseline in subjects treated with tapentadol (p < 0.001). Tapentadol is effective in OA pain management in horses. Serotonin and cortisol may be utilized as biomarkers in the pain stress response. Serotonin can also determine the state of wellbeing of patients.